Applications and approaches to object-oriented software design emerging research and opportunities - Altan, Zeynep, 1958- (Advances in systems analysis, software engineering, and high performance computing (ASASEHPC) book series., 2020)
"This book explores applications and approaches to object-oriented software design"--